Vietnam : Overview of Tobacco Control Legislation, Use and Taxation - Marquez, Patricio V. (World Bank, Washington, DC, 2019)
This country brief presents an overview of current tobacco control legislation, use, and taxation policy in Vietnam. Data and information were collected from different sources. The brief is intended to serve as the context for complementary assessments on different aspects of tobacco taxation in the country to be shared with government teams and other national and international stakeholders. Vietnam is a party of Framework Convention on Tobacco Control, and its legislation contains several effective measures aimed to curb the tobacco epidemic. There is a growing consensus in the country about the need for the government to strengthen tobacco control to protect the population from health risks associated with tobacco use. However, the state-ownership of tobacco industry poses a major paradox within the government that benefits from the manufacturing of tobacco products and is also responsible for controlling tobacco consumption.The prevalence of smoking is high, especially among men. Although it was the highest in the world in the 1990, it has substantially declined since that period. However, over 35 percent of men are still regular cigarette smokers. While fewer than 2 percent of women smoke, women and children are exposed to high levels of second-hand smoke at home and in public places, and this exposure also harms and kills. It is estimated that 40,000 people are dying prematurely each year in Vietnam from tobacco-related diseases. In Vietnam, as in other countries across the world, smoking-related illnesses cost millions of dollars each year, both in terms of direct medical costs and productivity losses, imposing a heavy economic toll on households and governments.